Pengoptimalan Perawatan Kereta Untuk Meminimalkan Keterlambatan Perawatan Di Balai Yasa Manggarai - Alfaris, Arif; Muhardono, Muhardono; Ryanto, Azhar Hermawan (Politeknik Perkeretaapian Indonesia Madiun, 2019)
Balai Yasa Manggarai is a place to conduct periodic maintenance of railroad facilities. The train maintenance program at Balai Yasa Manggarai in the first quarter of 2017 every month maintenance occurs late in maintenance. To follow up on this problem, an analysis of maintenance support components is seen in terms of Human Resources, Maintenance Equipment, and Maintenance Facilities. Based on the analysis that has been done, it can be concluded that the needs of employees are in accordance with working hours but the competence of personnel does not meet the qualifications indicated by many who do not yet have a Certificate of Maintenance Expertise, there are many equipment that already have old age and maintenance facilities such as underpasses are not suitable because there are standing water that can interfere with the maintenance of the train. Based on the results of the analysis, it is hoped that train infrastructure operators will immediately implement competency enhancements for maintenance personnel, equipment and maintenance facilities in an effort to optimize train maintenance to minimize maintenance delays at Balai Yasa Manggarai